THE RELATIONSHIP BETWEEN OBESITY AND DIABETES - Bahtiyorovich, Asatullayev Rustam; qizi, Murodullayeva Rukhshona Jasur (Research Focus International Scientific Journal, 2026)
This article analyzes the relationship between obesity and diabetes. Studies show that excess weight and fat accumulation lead to insulin resistance and hormonal imbalance in the body, which increases the risk of developing diabetes. The article scientifically reviews different types of obesity, methods of their assessment, and their impact on diabetes. It also analyzes prevention and treatment strategies, including the importance of proper nutrition physical activity, and lifestyle changes. This article helps to understand the complex mechanisms between obesity and diabetes and to identify preventive and health-promoting measures.